A new specimen of Lariosaurus xingyiensis (Reptilia, Sauropterygia) from the Ladinian (Middle Triassic) Zhuganpo Member, Falang Formation, Guizhou, China. Issue 2 (4th March 2017) - Lin, Wen-Bin; Jiang, Da-Yong; Rieppel, Olivier; Motani, Ryosuke; Ji, Cheng; Tintori, Andrea; Sun, Zuo-Yu; Zhou, Min
ABSTRACT: A new specimen of Lariosaurus xingyiensis is described and provides new information on the dermal palate of the skull and the postcranial skeleton. Based on a comprehensive comparison with the holotype specimen, an amended diagnosis of L. xingyiensis is given on the basis of the following features: a medium-sized species of Lariosaurus with jugal absent, longitudinal diameter of upper temporal fenestra about 1.7 times longitudinal diameter of orbit, retroarticular process elongate, clavicles without anterolaterally expanded corners, posterior scapular process (blade) slender and elongate, humerus distinctly shorter than femur, and dorsal process of ilium with distinct tubercular ornamentation. Two phylogenetic analyses of Nothosauridae demonstrate that Nothosaurus as previously conceived is not monophyletic whereas Lariosaurus is a monophylum. Three species previously referred to Nothosaurus are more closely related to Lariosaurus and are hereby reassigned to Lariosaurus, namely, L. juvenilis, L. youngi, and L. winkelhorsti . SUPPLEMENTAL DATA—Supplemental materials are available for this article for free at www.tandfonline.com/UJVP Citation for this article: Lin, W.-B., D.-Y. Jiang, O. Rieppel, R. Motani, C. Ji, A. Tintori, Z.-Y. Sun, and M. Zhou. 2017. A new specimen of Lariosaurus xingyiensis (Reptilia, Sauropterygia) from the Ladinian (Middle Triassic) Zhuganpo Member, Falang Formation, Guizhou, China. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1278703.